Pengaruh Beban Kerja terhadap Kinerja dengan Work Life Balance sebagai Variabel Mediasi (Studi pada Pegawai DPRD Kab. Ngawi) - Erlina Ambar Anggita Putri; Rasistia Wisandianing Primadineska (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to determine the effect of workload on performance with work life balance as a mediating variable for DPRD employees in Ngawi Regency. The population in this study were all employees of the DPRD of Ngawi Regency, using a non-probability sampling technique with a saturated sample technique. The number of respondents in this study were 80 employees. Data collection was carried out by distributing questionnaires. Instrument tests, normality tests, classical assumption tests were carried out and all met the criteria. The hypothesis test in this study used regression analysis and bootstrapping Process macro v3.0 for SPSS 26 proposed by Andrew. F. Hayes. The results showed that workload has a negative effect on performance, workload has a positive effect on work life balance, work life balance has a positive effect on performance, and work life balance is able to mediate the effect of workload on performance. The effect of workload on performance with work life balance as a mediating variable is indicated by an Adjusted R Square value of 10.8% and the remaining 89.2% is influenced by other variables not examined in this study.